Improvement of speed perception in driving simulators using image deformation based on the human visual space - Takafumi ASAO (The Japan Society of Mechanical Engineers, 2020)
Driving simulators (DSs) have been widely used to develop advanced driver assistance systems to improve driving safety in vehicles. A major drawback of using DSs is the lack of speed perception while driving. Hence, improvements to speed perception have been recognized as a major priority for enhancing DSs. One approach for achieving better speed perception is to manipulate the human visual space using distorted images in DSs. A previous study revealed that the visual space was distorted subjecting to a visual distance towards an object in a virtual space. Thus, this study aims to obtain optimized image distortions and to evaluate their ability to allow drivers to perceive speed more accurately. A set of computer graphic images representing driving in a straight rural-like road was generated by applying distortions to the original image. The first experiment was conducted to determine the participants’ perceived speeds when viewing the images. Four levels of image distortion were used on seven images representing different speeds. The perceived speed increased with the image distortion, and an equation defining the perceived speed as a function of both image speed and distortion was derived. Another experiment was then conducted to verify whether the images generated using the derived equation could allow drivers to accurately perceive speed. As a result, the optimized image distortion allowed the DS users to accurately determine the image speeds, with an average difference between the perceived and the image speed of 2.7%.